MENINGKATKAN KEMAMPUAN MEMBACA ANAK MELALUI MEDIA KARTU ABACAGA : PENELITIAN TINDAKAN KELAS PADA KELOMPOK B DI SPS MEKAR KARYA IV BABAKAN BARU TAHUN AJARAN 2024/2025 - Jurtini Jurtini; Ibnu Hurri; Elnawati, Elnawati (CV. ADIBA AISHA AMIRA, 2025)
This study aims to improve the reading skills of early childhood children through ABACAGA card media in Group B SPS Mekar Karya IV Babakan Baru. Reading ability is a basic skill that plays an important role in children's cognitive development and their readiness to enter further education. Based on initial observations, it was found that many children still have difficulty in recognizing letters, composing words, and reading fluently. The lack of interesting learning methods is also a factor in children's low interest in reading. The research method used is Classroom Action Research (CAR) with the Kemmis and McTaggart model, which consists of two cycles. Each cycle includes the planning, implementation, observation, and reflection stages. The subjects of the study were children in group B at SPS Mekar Karya IV Babakan Baru. Data were collected through observation, interviews, and documentation. The results showed that the use of ABACAGA cards can significantly improve children's reading skills. At the pre-cycle stage, children's reading skills were still low, but after being given intervention through ABACAGA card media, there was a significant increase in letter recognition, words, and simple reading comprehension. This media has proven effective in attracting children's interest and motivating them to learn to read in a more interactive and enjoyable way. Therefore, this study provides encouragement for educators, especially PAUD teachers, in implementing more innovative learning methods. In addition, this study can also be a reference for further research in the field of early childhood literacy.